PENGARUH BEBAN KERJA, MOTIVASI KERJA, DAN KUALITAS HIDUP KERJA TERHADAP KETERIKATAN KARYAWAN Pada PPSU Cempaka Baru, Jakarta Pusat - Naufal Rafi Dzulfikar (2023)
This research used a quantitative method, conducted at PPSU in the Cempaka Baru sub-district, Central Jakarta. This study aims to determine and prove the effect of workload, work motivation, and quality of work life on employee engagement. The sampling technique used was all data from the population, so that a sample of 57 officers was obtained. Data collection was carried out through distributing questionnaires. The data analysis technique used is the Partial Least Square (PLS) method. The test results obtained in this research (1) workload has a negative and significant effect on employee engagement (2) work motivation has a significant effect on employee engagement (3), quality of work life has a significant effect on employee engagement. The implication of this research is theoretically. Information in research is expected to add insight in the development of knowledge in the field of human resource management, as material for thought and consideration in solving existing problems. The contribution in this study is to assist officers in overcoming problems, especially in terms of workload, work motivation, and quality of work life on employee engagement.